The Current Czech-Italian Cooperation in the Aerospace Industry and the Partnership’s Challenges - Gasparini, Amedeo (2022)
The aerospace industry has experienced increase importance for the Czech Republic and Italy. Both economies have many companies dealing with aerospace strategic sectors and entertain partnerships and agreements, through a network ranging from research to industry. High-qualified medium-size companies have become crucial players in the aerospace industry of both countries. Czechia and Italy integrate their local with international reality. A wide universe of small enterprises dealing with satellites, tech, digital tools all dedicated to the development and implementation of aerospace projects, with a close orientation to the future challenges of the aerospace industry, characterizes the current Czech-Italian relations in the field of the aerospace industry. And it is important for the future of both Czechia and Italy, as well as an example for other countries for a new partnership in the sector.